Hypo-methylation mediates chromosomal instability in pancreatic NET. Issue 3 (March 2017) - Marinoni, I; Wiederkeher, A; Wiedmer, T; Pantasis, S; Di Domenico, A; Frank, R; Vassella, E; Schmitt, A; Perren, A
Abstract : DAXX and or ATRX loss occur in 40% of pancreatic neuroendocrine tumors (PanNETs). PanNETs negative for DAXX or ATRX show an increased risk of relapse. The tumor-associated pathways activated upon DAXX or ATRX loss and how this event may induce chromosomal instability (CIN) and alternative lengthening telomeres (ALT) are still unknown. Both DAXX and ATRX are involved in DNA methylation regulation. DNA methylation of heterochromatin and of non-coding sequences is extremely important for the maintenance of genomic stability. We analyzed the association of DAXX and/or ATRX loss and CIN with global DNA methylation in human PanNET samples and the effect of DAXX knock-down on methylation and cell proliferation. We assessed LINE1 as well as global DNA methylation in 167 PanNETs, and we found that DAXX and or ATRX-negative tumors and tumors with CIN were hypomethylated. DAXX knock-down in PanNET cell lines blocked cells in G1/G0 phase and seemed to increase CIN in QGP-1 cells. However, no direct changes in DNA methylation were observed after DAXX knock-down in vitro . In conclusion, our data indicate that epigenetic changes are crucial steps in the progression of PanNETs loss and suggest that DNA methylation is the mechanism via which CIN is induced, allowing clonal expansion and selection.